Development of in vitro test battery to predict toxicity of indoor air - Ahoniemi, Jonna (My University, 2019)
The impurities of the air inside the buildings and the resulting health issues have become an increasing problem. Impurities of indoor air may cause various symptoms, such as respiratory symptoms, nausea, fatigue and memory impairment. There is a lack of reliable, efficient and standardized methods for testing the potential effects of the air impurities on humans. In this study three different cell types (normal human bronchial epithelial cells, human BJ fibroblasts, and THP-1 cells differentiated with PMA-method toward macrophages) are exposed to condensed water indoor air samples, and four positive controls (2,4-dinitrochlorobenzene, Nickel (II) sulphate hexahydrate, Triclosan and Sodium Dodecyl Sulfate) in order to investigate potential cell-specific effects. The viability of exposed cells is tested using both neutral red uptake (NRU) and Water Soluble Tetrazolium Salt -1 (WST-1) assays as endpoints. Within the research group also cytokine production from THP-1 macrophages after exposure to the indoor air samples, as well as the stability of the indoor air samples are studied. The results suggest that indoor air toxicity testing using freshly collected liquid samples, THP-1 macrophages and WST-1 assay is a promising method and could bring needed variety to study indoor air quality. It is also cost-efficient and therefore could be used in large and complex buildings to assess indoor air. Dinitrochlorobenzene and Nickel (II) sulphate hexahydrate meets the standards for positive controls in indoor air testing. Although the results from cytokine production are preliminary, the results suggest that also cytokine measurement has potential to detect toxicity in indoor air.